2019
DOI: 10.21315/eimj2019.11.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Levels and Attitudes of Medical Faculty Personnel on Traditional and Complementary Medicine

Abstract: There is no any regular and standardised traditional and complementary medicine (T&CM) training intended for the public or personnel in medical faculties or other institutions and organisations related to health care in Turkey. In this study, knowledge level and attitudes of medical faculty personnel on T&CM were investigated. This study is a cross-sectional survey study. A survey that consists of 12 questions investigating the knowledge and attitudes on T&CM as well as six questions for sociodemographic data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
1
6
0
5
Order By: Relevance
“…Consistent with this finding, a 2020 study in China concluded that medical students preferred media (39.3%) over teachers (32.1%) for obtaining information on CAM. Similar results were reported in other studies conducted in Turkiye (Ayraler et al, 2020) and in other countries (Hua, Fan, Dong, & Sherer, 2017). Presently, media is a major access point to information, and this leads to a situation where the accuracy of the information on the media should be questioned.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with this finding, a 2020 study in China concluded that medical students preferred media (39.3%) over teachers (32.1%) for obtaining information on CAM. Similar results were reported in other studies conducted in Turkiye (Ayraler et al, 2020) and in other countries (Hua, Fan, Dong, & Sherer, 2017). Presently, media is a major access point to information, and this leads to a situation where the accuracy of the information on the media should be questioned.…”
Section: Discussionsupporting
confidence: 87%
“…According to the data obtained in this research, cupping (blood letting) was the most well-known method among midwifery students, and acupuncture was the most well-known method in women's healthcare (Table 2). Ayraler et al (2020) reported that the most well-known method was cup application (Ayraler, Öztürk, Oruç, & Yavuz, 2020), whereas the CAM methods mostly used by nurses were massage, herbal medicine, and mind-body therapies (Balouchi et al, 2018). Students are probably familiar with these practices as they are included in the curriculum of labor and delivery courses as part of nonpharmacological methods used to relieve pain.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the survey studies conducted with medical faculty students revealed that the rate of hearing about homeopathy practice varied between 6.2% and 26.7%. 16,18,[20][21][22][23] In a study conducted with the students of a health vocational school, it was determined that the rate of hearing about homeopathy was 6.4%. 24 In a study evaluating the awareness of TCM practices among pharmacy faculty students, the rate of being aware of homeopathy was 21.1%.…”
Section: Discussionmentioning
confidence: 99%
“…29 47.0% of pharmacy students expressed interested in learning more about homeopathy or applying it in their careers. When compared to studies conducted on medical faculty students in the literature, 21,23 pharmacy faculty students included homeopathy in their future career planning at a higher rate. This may be due to the intense content of training on TCM and homeopathy practices in the pharmacy faculty curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…Another domestic study demonstrated that cupping, acupuncture and hypnosis were the most preferred method among the participants, whereas chiropractic care and prolotherapy were the least. [16] A study conducted in Indonesia reported spiritual-religious therapy, dietary supplements, music therapy and meditation as the most preferred TCAM methods among the participants, respectively. [17] TCAM therapies provide an optimistic outlook and touch individuals' feelings and spirituality, going beyond the 'symptoms' defined by conventional medicine.…”
Section: As Seen Inmentioning
confidence: 99%